Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1210/mend-5-2-226
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofreg/PSP, a Pancreatic Exocrine Gene: Relationship to Changes in Islet β-Cell Mass

Abstract: A cDNA termed reg was recently isolated by differential screening of a library prepared from regenerating islets isolated from pancreatic remnants of rats subjected to 90% pancreatectomy and nicotinamide treatment. This led to speculation that this gene may be involved in expansion of beta-cell mass. In the current study we have measured reg expression after implantation and resection of a solid insulinoma tumor into rats, maneuvers known, respectively, to reduce and reexpand the volume of beta-cells in the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 24 publications
2
45
1
1
Order By: Relevance
“…*p Ͻ 0.05 compared with both the control and single-dose groups. for RegI in cellular proliferation is well demonstrated in pancreas (Francis et al, 1992;Miyaura et al, 1991;Watanabe et al, 1994), and RegI has also been implicated as exerting trophic effects on the gastric epithelium (Asahara et al, 1996;Fukui et al, 1998;Higham et al, 1999;Kawanami et al, 1997;Kazumori et al, 2000). Moreover, our results show clear evidence of concordantly increased expression of RegI and PCNA in both damaged and healing gastric epithelium.…”
Section: Alderman Et Alsupporting
confidence: 74%
“…*p Ͻ 0.05 compared with both the control and single-dose groups. for RegI in cellular proliferation is well demonstrated in pancreas (Francis et al, 1992;Miyaura et al, 1991;Watanabe et al, 1994), and RegI has also been implicated as exerting trophic effects on the gastric epithelium (Asahara et al, 1996;Fukui et al, 1998;Higham et al, 1999;Kawanami et al, 1997;Kazumori et al, 2000). Moreover, our results show clear evidence of concordantly increased expression of RegI and PCNA in both damaged and healing gastric epithelium.…”
Section: Alderman Et Alsupporting
confidence: 74%
“…Reg gene expression was observed in regenerating pancreatic islets from depancreatized rats, but not in normal ones. Subsequent studies have demonstrated that enhanced reg gene expression is linked to DNA synthesis in pancreatic islets (9,10). Immunocytochemistry has revealed that Reg protein is synthesized in and secreted from the regenerating beta cells and that its expression is closely associated with the regeneration of beta cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the discrepancies between human and animal data could be the fact that reg gene overexpression could be a very transient phenomenon. In various animal models of islet regeneration, reg gene overexpression occurs very early in pancreas (1-2 days) and lasts only a few days (less than 1 week) (8)(9)(10)(11). In our series, it is noteworthy that three patients in both prediabetic and diabetic groups exhibited transient high serum reg levels.…”
Section: Journal Of Endocrinology (1999) 141mentioning
confidence: 60%
“…Indeed, measurement of reg protein might be a good candidate for this purpose. The reg protein is normally secreted by exocrine pancreatic cells and reg gene overexpression has previously been shown to be associated with regeneration of pancreatic islets (8)(9)(10)(11). In animal models of autoimmune diabetes, pancreatic overexpression of reg mRNA has been reported (12)(13)(14) during active phases of diabetogenesis and reg gene proposed to play a role in the destruction/regeneration process during autoimmune aggression of beta cells (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%